MANAGING MULTIPLE CHALLENGING ROLES: FAMILY, WORK AND PROFESSIONAL DEVELOPMENT - USM ADMIN (Moldova State University, 2018)
In the modern society, as researchers remarked, it is common to work and study at the same time, thus, academic and work domains are interdependent and influence each other continuously, frequently provoking inter-role conflict situations. In some cases, the conflict of the role can acquire a three-dimensional nature when work, family, and education come at play concomitantly. The strain may arise in this case from the difficulty to juggle these three roles and manage time properly while trying to pursue studies successfully, accomplish professional tasks in an efficient manner and fulfil responsibilities related to parenthood, marriage or private life. In this paper, we have proposed a case study of such triple role conflict (work-family-education) in the local academic context. We have conducted 14 in-depth interviews with junior members of academic staff that experience this three-dimensional conflict (PhD students with teaching duties, married, having small children). Our interest was to identify their perceptions concerning these conflictual experiences, the level of one or another role commitment, and their evaluations with reference to severity of conflict and its consequences on the academic results and efficiency, as well as the strategies used in order to manage this conflict. Keywords: work-family-education conflict, work-life balance, university, academic career, PhD students.